Measuring patient quality of life following treatment for alopecia - Kunlawat Thadanipon (2022)
Alopecia is a challenging problem for both physicians and patients in terms of diagnosis and treatment. Alopecia usually has negative effects on patients’ emotional and psychological well-being. Several studies have examined the effect of alopecia on patients’ health-related quality of life (HRQoL) and have consistently reported poor scores. However, deeper insight into the impact of alopecia on affected individuals and its measurement using HRQoL questionnaires is lacking in the literature. In this article, the methods for measuring the HRQoL of patients with alopecia were comprehensively reviewed. Their applications and limitations were also discussed.